Kommunikationsstrategi för Renbruksplan : är det en fungerande modell för samebyarna vid samråd? - Vestman, Hanna; Wennström, Ragna (SLU/Dept. of Forest Ecology and Management, 2012)
The reindeer planning system (Renbruksplanen, RBP) is a communication and planning tool designed for Sami groups. A key purpose of this is that it will act as a tool in consultation with other market players, including forestry. Sami groups have asked for a model of how this can be used in a flexible manner. With the Swedish Forest Agency as a project manager, a communication model for how to use the RBP has been designed. It consists of a number of points divided into ”before”, “during” and “after” the consultation. Interviews with selected Sami groups in Västerbotten have been the base to this evaluation of the model's effectiveness. The communication model is a well designed tool, but has not been actively used that much. The reason for this is that many groups isn’t sufficiently complete with their RBP to use this in consultation, as well as the communication model recently been published. Many groups use unconsciously parts of the model at the consultations. The interest in education of the use of RBP is large.